THE IMPACT OF INFORMALITY ON SOCIAL SECURITY CONTRIBUTIONS AND WORKERS’ SOCIAL PROTECTION - dos Santos, Rodrigo Andrade (Seven Editora, 2026)
Informality in the Brazilian labor market represents one of the main challenges to the sustainability of the social security system. Millions of workers perform activities without formal registration, remaining deprived of labor rights and social security benefits, such as retirement, sick pay, and survivor’s pension. This reality results from factors such as unemployment, low professional qualification, bureaucracy, high formalization costs, and the expansion of the gig economy. In addition to compromising the future of workers, informality reduces public revenue and limits social investments. Given this scenario, it becomes essential that informal workers seek alternative forms of financial protection, contributing to the National Institute of Social Security (INSS) and joining supplementary pension plans in order to guarantee security and dignity in retirement. DOI: https://doi.org/10.56238/sevened2025.040-014